Resíduos de antiparasitários e agrotóxicos em leite bovino no rio grande do norte - Moreira, Josué de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Antiparasitics and pesticides residues are expelled through the milk, what may affect consumers’ health. The aim of this research was to determine the presence of antiparasitics’ residues and pesticides on the cows’ milk produced in Rio Grande do Norte. A quantity of 35 samples of milk were collected, being 15 whole pasteurized, formally commercialized, and 20 raw milk, informally commercialized. In order to detect antiparasitics residues, the Liquid Chromatography coupled with Mass Spectrometry (LC-MS/MS) method was carried, as well as the and Gas Chromatography coupled with Mass Spectrometry (GC-MS/MS) method was used to detect pesticides residues. After data analysis, no antiparasitic residues were found on the analyzed samples. Regarding the pesticides determination, the 23 milk analyzed samples were considered adequate, being under the Maximum Residue Limits (MRL). Pesticides residues were detected and quantified in five (22%) milk samples, being three (60%) in whole pasteurized milk and two (40%) in raw milk, with seven (6,6%) chemical compounds. Pesticides like flusilazole, penconazole and tebufenpyrad, that are prohibited, were found on the milk, what can be a warning related to the quality of the product and the consumers health, as well as the need of a more efficient control system in what regards the entry and trading of these products in Brazil
Keywords: Leite bovino; Resíduos de agrotóxicos; Antiparasitários; Contaminação; Cow’s milk; Pesticides Residues; Antiparasitics; Contamination; CIENCIAS AGRARIAS::MEDICINA VETERINARIA